1995
DOI: 10.1093/ajcn/62.6.1535s
|View full text |Cite
|
Sign up to set email alerts
|

Growth retardation in human cervical dysplasia-derived cell lines by beta-carotene through down-regulation of epidermal growth factor receptor

Abstract: We used newly established cervical dysplasia-derived cell lines to elucidate a molecular mechanism of the preventive action of beta-carotene in cervical multi-step carcinogenesis. Liposomal beta-carotene was added to the culture medium for human cervical dysplasia cell lines, CICCN-2 from cervical intraepithelial neoplasia grade I (CIN I), CICCN-3 from CIN II, and CICCN-4 from CIN III, and human cervical carcinoma-derived cell lines such as CICCN-6, CICCN-18, and HeLa cells. beta-Carotene (10 mumol/L) induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Muto et al suggested that¯-carotene may prevent cervical carcinogenesis by inducing apoptosis in premalignant cervical dysplastic cells via down-regulation of epidermal growth factor receptor (32). We reported pro-apoptotic effects of canthaxanthin in both human colon adenocarcinoma and melanoma cells (33).…”
Section: Effects On Cell Proliferation Differentiation and Apoptosismentioning
confidence: 50%
“…Muto et al suggested that¯-carotene may prevent cervical carcinogenesis by inducing apoptosis in premalignant cervical dysplastic cells via down-regulation of epidermal growth factor receptor (32). We reported pro-apoptotic effects of canthaxanthin in both human colon adenocarcinoma and melanoma cells (33).…”
Section: Effects On Cell Proliferation Differentiation and Apoptosismentioning
confidence: 50%
“…Vitamin A, carotene or synthetic retinoids are capable of producing apoptosis in rat colonic tumor cells, 35 human prostate 36 and cervix, 37 and bovine mammary cells. 38 At least part of this effect may be mediated through the ability of the retinoids to block the effect of growth factors such as insulin-like growth factor-1 (IGF-1).…”
Section: Discussionmentioning
confidence: 99%
“…In one of the earliest reports, b-carotene derived from Dunaliella was able to induce apoptosis in a preneoplastic cervical line, but not in a carcinoma-derived line (Muto et al, 1995;Toba et al, 1997). A differential effect of lutein on apoptotic pathways was reported for the MCF-7 mammary carcinoma cell line, SV40 transformed mammary cells, and normal human mammary cells.…”
Section: Growth Inhibitionmentioning
confidence: 97%